1998
DOI: 10.1161/01.cir.98.20.2160
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lead Selection and Population on Automated Measurement of QT Dispersion

Abstract: Background —The study of QT dispersion (QTd) is of increasing clinical interest, but there are very few data in large healthy populations. Furthermore, there is still discussion on the extent to which QTd reflects dispersion of measurement. This study addresses these problems. Methods and Results —Twelve-lead ECGs recorded on 1501 apparently healthy adults and 1784 healthy neonates, infants, and children were used to derive normal limits of QTd and QT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 43 publications
8
73
1
3
Order By: Relevance
“…QT d is significantly different between patients with a wide and a narrow T-wave loop, and a correspondence has been observed between QT d and the T-wave loop morphology (Kors et al 1999) rather than with VRD. In addition, similar QT d values have been measured on the standard 12-lead ECG and on synthesized 12 leads from the orthogonal XYZ leads, which intrinsically leave out regional repolarization heterogeneity (Macfarlane et al 1998). As a result, this QT d concept has been largely abandoned as a marker of VRD.…”
Section: (A ) Dispersion Of Repolarization Reflected On Ecg Intervalsmentioning
confidence: 89%
“…QT d is significantly different between patients with a wide and a narrow T-wave loop, and a correspondence has been observed between QT d and the T-wave loop morphology (Kors et al 1999) rather than with VRD. In addition, similar QT d values have been measured on the standard 12-lead ECG and on synthesized 12 leads from the orthogonal XYZ leads, which intrinsically leave out regional repolarization heterogeneity (Macfarlane et al 1998). As a result, this QT d concept has been largely abandoned as a marker of VRD.…”
Section: (A ) Dispersion Of Repolarization Reflected On Ecg Intervalsmentioning
confidence: 89%
“…When analyzing according to gender GF and GM groups had similar QTd levels. Reports show either no statistically significant difference in QTd between the genders (34). Compared to the GS and control subgroups, the GF group had significantly lower QTd than the CM group.…”
Section: Comparison Of Pd Qtd and Hr Values Between Gs And Control Gmentioning
confidence: 93%
“…In a population-based study involving 3285 adults and children by Macfarlane et al suggested that QT dispersion ≤50 ms indicated normality (15).…”
Section: Electrocardiographymentioning
confidence: 99%